Pendidikan Nasional Berbasis Aksiologi - Zulfahmi, Muhammad Riko Yohansyah; Aprison, Wedra (SUKMA: Jurnal Pendidikan, 2023)
The function of national education is to develop the ability to think rationally and form noble character in relation to Pancasila values, namely religious values, humanity, unity, democracy and justice. Axiology is a branch of philosophy that examines the benefits or values of knowledge acquired by humans. One branch of axiology is moral conduct (moral action that gives rise to discipline, especially ethics). Environmental ethics are guidelines on ways of thinking, behaving and acting based on positive values in order to maintain the function and sustainability of the environment. The axiological foundation of the national education system is important as a basis for analyzing the application of educational theory related to educational goals, especially in relation to Pancasila values. This study describes the benefits or values of axiology and its application in National Education. The conclusion of this study is that from an axiological perspective, the benefits of applying axiology to the environment in education that are expected to emerge are the awakening of students' conceptual knowledge about axiology-based national education, the development of procedural knowledge to develop students' skills and capacities in applying axiological principles, students are encouraged to develop their personalities to become wise and moral human beings with care for education, the realization of educational interventions for better conditions of students, successful in developing the attitudes and beliefs of students to try to become human beings with knowledge, skills, attitudes, and environmentally sound values to shape a sustainable future for future generations.